NECROTISING OTITIS EXTERNA: AN OVERVIEW OF IMAGING MODALITIES - Khan, Hammaad (Journal of Ayub Medical College Abbottabad, 2022)
Necrotising Otitis Externa (NOE) has often posed some challenges in view of diagnosis and management by clinicians. One such challenge is the appropriate and timely use of imaging techniques, since its use is critical not only in diagnosis but also determining the extent and resolution of the disease. Hence, doctors in both primary and secondary health care need to be familiar with presenting symptoms, while specialists need to be appraised of advances in imagining techniques in management of NOE. Whilst there is a general consensus amongst clinicians on some aspects of management of NOE, there is very limited consensus on the use of imaging modalities. There is no single modality of imaging that can provide a complete picture of diagnosis, disease progression and resolution. There are some advantages and limitation of each methodology, which indicate that a multi-modal imaging technique at particular stages of the disease may provide better management outcomes. However, further research in this area is required, as there is not yet an established '˜gold standard' for imaging in NOE. Keywords: Necrotising Otitis Externa; Malignant Otitis Externa; Skull base Osteomyelitis; Tc-99m bone scan; Ga-67 bone scan; Indium 111 labelled leukocyte scanning; SPECT